(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to evaluate the cognitive decline and its association with the oral health condition through the number of remaining teeth (NRT) and related oral maintenance and rehabilitation (OMR). Material and Methods: This study was classified as observational,cross-sectional and prospective. The oral examination included the NRT and OMR. The mental health status was obtained through the Mini‐Mental State Examination (MMSE). Other parameters included the American Society of Anesthesiologists Classification (ASA) modified for Dentistry, a handheld electrocardiogram (ECG) and blood tests. Results: The sample was composed with 63 patients. It was found correlation between NRT and MMSE scores (p= 0.01). Healthy patients (ASA I) have more teeth when compared to unhealthy (p=0.004). When better was the OMR, better was the scores of MMSE (p< 0.001) and better was the health status (p=0.004). Conclusion: The findings showed several associations between oral condition, systemic health and cognitive decline. Decreased NTR and compromised oral maintenance and/orrehabilitation was more frequently observed in patients classified as systemically unhealthy and with reduced MMSE scores.